Students' reading comprehension skills of science and physics texts - Wahyuni Handayani; Wawan Setiawan; Parlindungan Sinaga; Andi Suhandi (Jurnal Inovasi Pendidikan IPA, 2018)
Reading comprehension of physics texts is a neglected area in physics curricula. This article reports an investigation the critical reading of physics texts among students of physics education. Students’ performance reading comprehension on science text were investigated using reading comprehension test. Students’ reading comprehension of science texts are tested with the help of reading comprehension which is designed with reference to TOEFL reading test and translated into Bahasa Indonesia. Eight component skills of comprehension were examined. To assess the skill a reading comprehension of physics texts, true-false-unreported tests were used. It was found that the skill required to discriminate unreported statements from the others (true and false) was found to be of a higher level. Total of 67 students of physics education  at a college in Bandung  participated  in the study. It was found that students’ reading comprehension of science texts and physics texts were at lower level. These findings support the importance of incorporating training of reading comprehension strategy of the science text into the curricula.